Automated train track misalignment detection system based on inertia measurement unit - Hong, K.C. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents a feasible, portable and lowcost detection technique for train track misalignment by using a micro electro mechanical system-based inertial measurement unit (IMU). As the train track serves as the steering base for railway vehicles, sensor measurements from IMU reflects the interaction between train and its track, as well as enhances identification of potential misaligned track. A field testing was conducted on a passenger-loaded Electric Train Service (ETS), covering from Kampar Station to KL Sentral Station in Malaysia. These measurements were analyzed and presented with discussion on track characteristics, train motion and noise. The end-product of this system attempts to identify the location of potential misaligned tracks, improve train track maintenance system and enhance riding comfort for the passengers. Â© 2014 IEEE.